Ergonomic Applications Reduce Fatigue, Musculoskeletal Complaints, Heat Radiation, and Increase Productivity of Pig Rollers - Ardiyanti, Ni Putu; Purnawati, Susy; Adiputra, Nyoman; Dinata, I Made Krisna; Priambadi, I Gusti Ngurah (Green Publisher Indonesia, 2022)
One of the typical Balinese culinary tours is Pig Rollers. The process of making pig guling still on human power in the rolling process by doing a continuous circular motion. This study aims to determine the decrease in fatigue, musculoskeletal complaints, heat radiation, and increase in productivity before and after treatment of pig roller workers due to the application of ergonomics applications in the form of repairing work stations. The method used in this study is an experimental (true experimental) with the same subject design (treatment by subject design) and a randomized pre and post-test group design pattern of variables in the form of worker fatigue which is recorded with a 30 Items of Rating Scale of General Fatigue questionnaire; musculoskeletal complaints of workers who were recorded with the Nordic Body Map questionnaire; heat radiation measured with 4ch K Thermometer SD Logger; and the productivity of pig rolling workers is assessed based on the output (weight of the product produced) divided by the input (work pulse) multiplied by time (time). Measurements were carried out before and after working in Period I and Period II on 12 samples for 1 month. The data obtained will be analyzed by paired t-tests at a significance level of 5%. The results showed that there were significant differences (p<0.05) in workload, fatigue, musculoskeletal complaints, heat radiation, and work productivity in Period I and Period II. Ergonomics application in the form of work station improvement reduces workload by 10.22%, fatigue by 13.46%, musculoskeletal complaints by 33.61%, heat radiation by 11.81%, and increases productivity by 78.50%. It can be concluded that the application of ergonomics in the form of repairing work stations can reduce workload, fatigue, musculoskeletal complaints, and radiation, and increase the productivity of pig rolling workers in Peliatan Village, Ubud, Gianyar, Bali.